ALSinhibiting herbicide seed treatments control Striga hermonthica in ALSmodified corn (zea mays) - Berner, D.K.; Ikie, F.O.; Green, J.M. (1997)
Seed treatments with two acetolactate synthase (ALS)-inhibiting herbicides, the sulfony- lurea herbicide nicosulfuron and the imidazolinone herbicide imazaquin, controlled the parasitic weed Striga hermonthica in corn. The XA-17 gene in ALS-modified P3180IR corn strongly reduced corn injury from herbicide seed treatments while another ALS modification was not effective. Combining seed treatment of ALS-inhibiting herbicides and ALS-modified corn with the XA-17 gene may offer a practical means for African growers to control Striga hermonthica